HUBUNGAN INDEKS MASSA TUBUH (IMT) TERHADAP DAYA TAHAN KARDIORESPIRASI PADA PEMAIN FUTSAL UNIVERSITAS BALI INTERNASIONAL - I Komang Arya Triguna; I Made Dhita Prianthara; Komang Tri Adi Suparwati (Jurnal Kesehatan, 2025)
Futsal is a sport that requires high physical fitness, especially good cardiorespiratory endurance to support player performance during matches. One indicator that can influence cardiorespiratory endurance is Body Mass Index (BMI), which describes a person's nutritional status and body composition. This study aims to investigate the relationship between BMI and cardiorespiratory endurance in futsal players at Bali International University. The research employed a quantitativeapproach with a cross-sectional design. The sample consisted of 30 participants selected based on inclusion and exclusion criteria. Cardiorespiratory endurance was measured using the Harvard step test, and body mass index was calculated using the BMI formula. The results of the Spearman rank test indicated a significant negative correlation between BMI and cardiorespiratory endurance (r = -0.504; p = 0.005). This means that as BMI increases, cardiorespiratory endurance decreases. Based on the study results, it can be concluded that there is a relationship between body mass index (BMI) and cardiorespiratory endurance in futsal players at Bali International University. Based on the study results, it can be concluded that there is a relationship between body mass index (BMI) and cardiorespiratory endurance in futsal players at Bali International University.